Analysis Of Public Housing Savings Policy From The Perspective Of Islamic Economics: Social Welfare And Distribution Justice - Ishak, Muhammad Nur (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study aims to analyze the People's Housing Savings (Tapera) policy from the perspective of Islamic economics, with a focus on social welfare and distribution justice. Islamic economics puts forward the principles of social welfare and distributive justice, which emphasizes the fulfillment of basic needs, spiritual and moral well-being, and the fair and equitable distribution of wealth. In this context, this study evaluates how Tapera's policies can be integrated with Islamic economic principles to achieve these goals. The research method used is a qualitative method with a descriptive-analytical approach. The data was collected through literature studies, analysis of policy documents, and in-depth interviews with Islamic economics and housing experts. The analysis was conducted to identify the suitability of Tapera's policies with Islamic economic principles and assess their impact on social welfare and wealth distribution. The results of the study show that Tapera's policies are in line with several Islamic economic principles, such as zakat, alms, and qard al-hasan, which aim to reduce economic disparities and promote social welfare. Tapera has succeeded in providing better access to housing for low- and middle-income people, improving their quality of life. However, the study also found some challenges, including limitations in fair distribution mechanisms and the need for greater transparency and accountability in fund management. Tapera's policy has great potential to support social welfare and distribution justice in accordance with Islamic economic principles. However, further efforts are needed to optimize the implementation of this policy to be more effective and efficient. This research provides practical recommendations for policymakers to strengthen aspects that are in line with Islamic values and overcome existing obstacles, with the ultimate goal of creating a more just and prosperous society